2020
DOI: 10.5851/kosfa.2020.e31
|View full text |Cite
|
Sign up to set email alerts
|

A Non-yeast Kefir-like Fermented Milk Development with Lactobacillus acidophilus KCNU and Lactobacillus brevis Bmb6

Abstract: The use of yeast assist kefir fermentation, but also can cause food spoilage if uncontrolled. Hence, in this study, the microbial composition of an existing commercial kefir starter was modified to produce a functional starter, where Lactobacillus acidophilus KCNU and Lactobacillus brevis Bmb6 were used to replace yeast in the original starter to produce non-yeast kefir-like fermented milk. The functional starter containing L. acidophilus KCNU and L. brevis Bmb6 demonstrated excellent stability with 10 10 CFU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Numerous studies have reported that consumption of fermented food helps in alleviating gastrointestinal disorder symptoms [ 28 , 29 , 30 , 31 , 32 ]. Notably, the functional microorganisms, especially those from the genera Bifidobacterium , Lactobacillus , Lactococcus , and Pediococcus , and their bioactive metabolites found in fermented food, have shown to having been responsible for these functions [ 19 , 20 , 28 , 30 , 31 , 32 , 33 , 34 , 35 ]. Hence, in this study, potential lactic acid bacteria were isolated from the local homemade fermented food, kimchi, to investigate their regulatory effects on alleviating colitis symptoms, especially on TJ recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported that consumption of fermented food helps in alleviating gastrointestinal disorder symptoms [ 28 , 29 , 30 , 31 , 32 ]. Notably, the functional microorganisms, especially those from the genera Bifidobacterium , Lactobacillus , Lactococcus , and Pediococcus , and their bioactive metabolites found in fermented food, have shown to having been responsible for these functions [ 19 , 20 , 28 , 30 , 31 , 32 , 33 , 34 , 35 ]. Hence, in this study, potential lactic acid bacteria were isolated from the local homemade fermented food, kimchi, to investigate their regulatory effects on alleviating colitis symptoms, especially on TJ recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms of DSS-induced mice are similar to those of patients with IBD, which include bloody stool, diarrhea, elevated inflammatory biomarkers, and drastic weight loss [ 43 ]. In our previous study, we reported that L. brevis Bmb6-containing fermented milk significantly improved the DAI score in DSS-induced mice [ 20 ]. This is in agreement with our current results which showed that the DAI score was significantly decreased in the Bmb6 group, with no drastic weight loss, and only non-forming hemoccult stools were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilai pH pada minuman susu fermentasi ini selaras dengan standar pH susu fermentasi secara umum yang juga diaplikasikan untuk yoghurt dan kefir, yaitu 4,0-4,5 (Lee et al, 2020). Nilai pH merupakan salah satu parameter keamanan pada produk minuman susu fermentasi.…”
Section: Hasil Dan Pembahasanunclassified
“…Dairy products, thanks to their rich and diversified composition, have very interesting therapeutic effects and regular consumption of these products can have an anticarcinogenic [3], antimicrobial [4], immunological effect very important [5] thanks to their very low final pH between 4.3 and 4.4 [6,7] without forgetting the beneficial effect on the intestinal tract [8].…”
Section: Introductionmentioning
confidence: 99%